Pumpkin rootstock improves the growth and development of watermelon by enhancing uptake and transport of boron and regulating the gene expression - Shireen, Fareeha (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.